Two blades of grass: the impact of the green revolution - Gollin, D; Worm Hansen, C; Wingender, A (University of Chicago Press, 2021)
We estimate the impact of the Green Revolution in the developing world by exploiting exogenous heterogeneity in the timing and extent of the benefits derived from high-yielding crop varieties (HYVs). We find that HYVs increased yields by 44% between 1965 and 2010, with further gains coming through reallocation of inputs. Higher yields increased income and reduced population growth. A 10-year delay of the Green Revolution would in 2010 have cost 17% of GDP (gross domestic product) per capita and added 223 million people to the developing-world population. The cumulative GDP loss over 45 years would have been US$83 trillion, corresponding to approximately one year of current global GDP.